2021
DOI: 10.3390/ijerph182413263
|View full text |Cite
|
Sign up to set email alerts
|

When Alcohol Adverts Catch the Eye: A Psychometrically Reliable Dual-Probe Measure of Attentional Bias

Abstract: Existing tasks assessing substance-related attentional biases are characterized by low internal consistency and test–retest reliability. This study aimed to assess the psychometric properties of a novel dual-probe task to measure alcohol-related attentional bias. Undergraduate students were recruited in June 2019 (N = 63; final N = 57; mean age = 20.88, SD = 2.63, 67% females). In the dual-probe task, participants were presented with simultaneous visual streams of adverts promoting either alcoholic or non-alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, most recently-detoxified patients already avoid alcohol-related cues, raising doubts on the usefulness of generalized attention training in this population. Importantly, the increasing accessibility of reliable AB measures by using low-cost eye-tracker or newly developed AB paradigms [52] helps clinicians to identify patients who will benefit most from attention training. Finally, the strong relationship between AB and craving observed here and previously [53] highlights the need to identify and target psychological factors triggering craving in SAUD to break the vicious circle between craving, AB and alcohol-seeking behaviour, traditionally described as the three pathways to relapse [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, most recently-detoxified patients already avoid alcohol-related cues, raising doubts on the usefulness of generalized attention training in this population. Importantly, the increasing accessibility of reliable AB measures by using low-cost eye-tracker or newly developed AB paradigms [52] helps clinicians to identify patients who will benefit most from attention training. Finally, the strong relationship between AB and craving observed here and previously [53] highlights the need to identify and target psychological factors triggering craving in SAUD to break the vicious circle between craving, AB and alcohol-seeking behaviour, traditionally described as the three pathways to relapse [54].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, alcohol marketing employ powerful visual cues that have been shown to heighten attentional bias and diminish inhibitory control (e.g., Maurage et al, 2020;Pennington et al, 2020;Wiechert et al, 2021). Research has also shown that alcoholrelated cues interfere with ongoing working memory processes (Gladwin & Wiers, 2012;Kessler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research indicates that these techniques work as intended: frequent exposure to alcohol advertisements is associated with more favourable evaluations, higher product recognition, and greater consumption (Jackson & Bartholow, 2020;Tanski et al, 2011;Wills et al, 2009). Branding has also been found to target the cognitive mechanisms implicated in alcohol consumption with brand logos heightening attentional bias and diminishing inhibitory control (Kreusch et al, 2013;Maurage et al, 2020;Pennington et al, 2020;Weafer & Fillmore, 2015;Wiechert et al, 2021). In light of the considerable influence of alcohol branding on consumer behaviour, we therefore hypothesised that the decoy effect would be greater for branded compared to unbranded alcoholic beverages.…”
Section: Introductionmentioning
confidence: 99%